Unravelling the mathematical tapestry: exploring the ethnomathematics of the “Seroa” within the Lakiput culture in Sarawak - Wong, Tze Jin; Suali, Melini; Chen, Chuei Yee; Magiman, Mohamad Maulana; Koo, Lee Feng; Chieng, Julia Chin Yee (Auricle Global Society of Education and Research, 2024)
This ethnomathematical study focuses on the intricate connections between mathematical principles and the rich palette of cultural craftsmanship, particularly Seroa, worn by the Lakiput people of Sarawak, Malaysia. Through a careful examination of geometric patterns, the study reveals the profound integration of mathematics and cultural identity inherent in the design and construction of this traditional craft. The study seeks to illuminate the unique mathematical language woven into the headdresses through a focused examination of material selection, proportion and ceremonial context. The collaboration with the Lakiput community not only enriches the research, but also contributes to a nuanced understanding of indigenous mathematical thought and promotes the preservation of cultural heritage in the intricate threads of tradition.